Endoscopic direct clipping versus indirect clipping for colonic diverticular bleeding: A large multicenter cohort study. Issue 1 (12th January 2022) - Kishino, Takaaki; Nagata, Naoyoshi; Kobayashi, Katsumasa; Yamauchi, Atsushi; Yamada, Atsuo; Omori, Jun; Ikeya, Takashi; Aoyama, Taiki; Tominaga, Naoyuki; Sato, Yoshinori; Ishii, Naoki; Sawada, Tsunaki; et al.
Abstract: Background: Direct and indirect clipping treatments are used worldwide to treat colonic diverticular bleeding (CDB), but their effectiveness has not been examined in multicenter studies with more than 100 cases. Objective: We sought to determine the short‐ and long‐term effectiveness of direct versus indirect clipping for CDB in a nationwide cohort. Methods: We studied 1041 patients with CDB who underwent direct clipping ( n = 360) or indirect clipping ( n = 681) at 49 hospitals across Japan (CODE BLUE‐J Study). Results: Multivariate analysis adjusted for age, sex, and important confounding factors revealed that, compared with indirect clipping, direct clipping was independently associated with reduced risk of early rebleeding (<30 days; adjusted odds ratio [AOR] 0.592, p = 0.002), late rebleeding (<1 year; AOR 0.707, p = 0.018), and blood transfusion requirement (AOR 0.741, p = 0.047). No significant difference in initial hemostasis rates was observed between the two groups. Propensity‐score matching to balance baseline characteristics also showed significant reductions in the early and late rebleeding rates with direct clipping. In subgroup analysis, direct clipping was associated with significantly lower rates of early and late rebleeding and blood transfusion need in cases of stigmata of recent hemorrhage with non‐active bleeding on colonoscopy, right‐sided diverticula, and early colonoscopy, but not with active bleeding on colonoscopy, left‐sided diverticula, or elective colonoscopy. Conclusions: Our large nationwide study highlights the use of direct clipping for CDB treatment whenever possible. Differences in bleeding pattern and colonic location can also be considered when deciding which clipping options to use.